ANALISIS KEBIJAKAN PENDIDIKAN ISLAM DALAM REGULASI SISTEM PENDIDIKAN NASIONAL KONTEMPORER - Sulaiman Sulaiman; Muhammad Riff'an Alghiffari; Putra Dwiki Reza (Eduvis : Jurnal Manajemen Pendidikan Islam, 2022)
Islamic education in Indonesia occupies a central yet complex position within the national education system, shaped by a layered regulatory framework that continues to evolve in response to political, social, and global dynamics. Despite formal legal recognition of Islamic educational institutions through national legislation, the implementation of these policies frequently reveals persistent tensions between Islamic educational ideals and the standardizing imperatives of national education governance. This study aims to analyze the position, substance, and implementation of Islamic education policies embedded within contemporary national education system regulations in Indonesia, while identifying critical policy gaps that demand scholarly and practical attention. Using a library research methodology, data were collected systematically from authoritative policy documents, relevant books, and reputable peer-reviewed journals published within the past five years. The findings indicate that while Islamic education has achieved significant formal recognition, structural inequalities, curriculum standardization pressures, and governance challenges continue to limit the transformative potential of Islamic educational institutions within the national system.